Modern management : diversity, quality, ethics and the global environment / [cakera padat] - 317497 Certo, Samuel C. (Upper Saddle River, N.J. : Prentice-Hall, 2000)
System requirement : Windows or MacOS, QuickTime, and an Internet browser.